Implications of COVID-19 Innovations for Social Interaction: Provisional Insights From a Qualitative Study of Ghanaian Christian Leaders - Adams, Glenn; Osei-Tutu, Annabella; Affram, Adjeiwa Akosua; Phillips-Kumaga, Lilian; Dzokoto, Vivian Afi Abui (Frontiers in Psychology, 2022)
Responses to the COVID-19 pandemic prompted people and institutions to turn to online virtual environments for a wide variety of social gatherings. In this perspectives article, we draw upon our previous work and interviews with Ghanaian Christian leaders to consider implications of this shift. Specifically, we propose that the shift from physical to virtual interactions mimics and amplifies the neoliberal individualist experience of abstraction from place associated with Eurocentric modernity. On the positive side, the shift from physical to virtual environments liberates people to selectively pursue the most fulfilling interactions, free from constraints of physical distance. On the negative side, the move from physical to virtual space necessitates a shift from material care and tangible engagement with the local community to the psychologization of care and pursuit of emotional intimacy in relations of one’s choosing—a dynamic that further marginalizes people who are already on the margins. The disruptions of the pandemic provide an opportunity to re-set social relations, to design ways of being that better promote sustainable collective well-being rather than fleeting personal fulfillment.